2004
DOI: 10.1590/s0103-97332004000400014
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and ordering in group-III nitride alloys

Abstract: The electronic, structural, and thermodynamic properties of cubic (zinc blende) group-III nitride ternary InxGa1−xN and quaternary AlxInyGa1−x−yN alloys are investigated by combining first-principles total energy calculations and cluster expansion methods. External biaxial strain on the alloys are taken into account in the calculations. While alloy fluctuations and strain effects play a minor role in the physical properties of AlGaN , due to the small lattice-mismatch, in the InGaN alloys we found a remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…One of the widely discussed features of InGaN compounds is the compositional inhomogeneity, which is usually considered as a compositional fluctuation or phase separation in the alloy growth [5][6][7][8]. Based on X-ray diffraction (XRD) and optical absorption studies, Singh and co-workers [5] provided a strong evidence of phase separation in InGaN thick films grown by molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely discussed features of InGaN compounds is the compositional inhomogeneity, which is usually considered as a compositional fluctuation or phase separation in the alloy growth [5][6][7][8]. Based on X-ray diffraction (XRD) and optical absorption studies, Singh and co-workers [5] provided a strong evidence of phase separation in InGaN thick films grown by molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…It should be added that we have here only considered some structural effects on materials with fixed atoms. Inclusion of thermal effects and strain will further complicate the investigations 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of In x Ga 1-x N compounds showed poor agreement of the DFT band gap values with experimental data [12,22,[40][41][42][43][44]. To improve consistency between theory and experiment, hybrid functionals in DFT have been used as an empirical simulation method.…”
Section: Methodsmentioning
confidence: 99%